2018
DOI: 10.1101/478461
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Network dynamics of Broca’s area during word selection

Abstract: 19 20 ¶ These authors contributed equally to this work. 21 22 23Current models of word-production in Broca's area posit that sequential and staggered semantic, 24 lexical, phonological and articulatory processes precede articulation. Using millisecond-resolution 25 intra-cranial recordings, we evaluated spatiotemporal dynamics and high frequency functional 26 interconnectivity between ventro-lateral prefrontal regions during single-word production. Through 27 the systematic variation of retrieval, selection, a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…Corresponding studies have suggested staged (Indefrey and Levelt, 2004 ) or overlapping (Riès et al, 2017 ; Conner et al, 2019 ) processes of lexical selection, phonological retrieval, and encoding, which mainly involve left lateralized fronto-temporal networks (Indefrey and Levelt, 2000 ; Binder and Desai, 2011 ; Robinson et al, 2012 ; Mirman et al, 2015 ). A recent connectivity analysis identified smooth transitions between an initial state modulating task-directed attention, possibly enabling activation spread, an early stage associated with lexical retrieval, a later stage associated with lexical selection and phonological encoding, and finally articulation, altogether indicating an interactive processing (Conner et al, 2019 ). VF, however, differs from picture naming in some regards, including the production of as many words as possible to only one stimulus and the prohibition of word repetition.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Corresponding studies have suggested staged (Indefrey and Levelt, 2004 ) or overlapping (Riès et al, 2017 ; Conner et al, 2019 ) processes of lexical selection, phonological retrieval, and encoding, which mainly involve left lateralized fronto-temporal networks (Indefrey and Levelt, 2000 ; Binder and Desai, 2011 ; Robinson et al, 2012 ; Mirman et al, 2015 ). A recent connectivity analysis identified smooth transitions between an initial state modulating task-directed attention, possibly enabling activation spread, an early stage associated with lexical retrieval, a later stage associated with lexical selection and phonological encoding, and finally articulation, altogether indicating an interactive processing (Conner et al, 2019 ). VF, however, differs from picture naming in some regards, including the production of as many words as possible to only one stimulus and the prohibition of word repetition.…”
Section: Discussionmentioning
confidence: 99%
“…This seems reminiscent of the activation of multiple concepts, which has been proposed to occur as a prerequisites of item selection (Indefrey and Levelt, 2004 ) in the course of word production. Spatiotemporal dynamics of the respective processes of word production have mainly been characterized for picture naming tasks (e.g., Billingsley et al, 2004 ; Indefrey and Levelt, 2004 ; Riès et al, 2017 ; Conner et al, 2019 ). Corresponding studies have suggested staged (Indefrey and Levelt, 2004 ) or overlapping (Riès et al, 2017 ; Conner et al, 2019 ) processes of lexical selection, phonological retrieval, and encoding, which mainly involve left lateralized fronto-temporal networks (Indefrey and Levelt, 2000 ; Binder and Desai, 2011 ; Robinson et al, 2012 ; Mirman et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The portion of temporal pole and MTG exhibiting alpha increases during the anticipatory window could be also involved in late-stage lexicoconceptual processing of adjectival representations, although given the relatively late postadjective window it is more likely to be related to anticipation. Relatedly, given increasing evidence for IFG involvement in linear morpho-syntactic processing and complex sentential syntax (Matchin and Hickok, 2020), as opposed to elementary syntactic structure building, it is also possible that the beta effect in pars triangularis indexes a form of lexical anticipation (for word frequency effects in pars triangularis via functional coupling with subcentral gyrus, see Conner et al 2019), with strictly syntactic anticipation being localized to temporal pole and MTG. A recent review of event-related potentials implicated in processing predictable words (the N400) also specifically pinpointed anterior IFG and LATL in preceding cortical activations (Pulvermüller and Grisoni, 2020), mapping onto the present results.…”
Section: Anticipatory Responsementioning
confidence: 99%